2012
DOI: 10.1080/11250003.2011.620638
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchytraeus anisodiverticulus, a new enchytraeid with enlarged ventral chaetae (Annelida, Clitellata) from north-eastern China

Abstract: Mesenchytraeus anisodiverticulus sp. nov. is described from north-eastern China. It is characterized by (1) enlarged ventral chaetae in segments V-VI (two per bundle); (2) nephridia with relatively developed interstitial tissue, occurring in five pairs in the preclitellar region; (3) a seminal vesicle occupying X-XVII, containing bulk of naked sperm bundles; (4) each spermatheca possessing two asymmetrical diverticula, attached entally to oesophagus in segment V; (5) atrium cylindrical, devoid of prostate glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…So far, arrangement of spermatozoa is a characteristic feature of this branchiuran which is not known in any other group of animals. A different pattern of broom‐like bundled arrangement of spermatozoa with uniformly aligned head and flagellum are found in the seminal vesicle of an annelid Mesenchytraeus anisodiverticulus (Shen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, arrangement of spermatozoa is a characteristic feature of this branchiuran which is not known in any other group of animals. A different pattern of broom‐like bundled arrangement of spermatozoa with uniformly aligned head and flagellum are found in the seminal vesicle of an annelid Mesenchytraeus anisodiverticulus (Shen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A series of field samplings were carried out from 2011 to 2020 on the northern slope of Changbai Mountain. The type locality of reported endemic Mesenchytraeus species can be found in the previous studies (Chen & Xie, 2015;Shen et al, 2011Shen et al, , 2012aShen et al, , 2012bZhang et al, 2018). The sampling sites of the specimens used in the study are as shown (Figure 1), there are four habitat types according to forest types: hardwood forest (S1, S2, P1), mixed forest (S3, S5, S6), spruce-fir forest (S7-S10, P2), and birch forest (S4).…”
Section: Study Area and Sitesmentioning
confidence: 99%
“…Michaelsen (1886) states that in M. beumeri Michaelsen, 1886, the developing spermatozoa remain enclosed by a fine membrane. Eisen (1904) was the first to describe and illustrate sperm bundles in different shapes in M. franciscanus Eisen, 1904. In recent years, there were sporadic reports about new species with different forms of regular sperm bundles, such as ball-shaped, flame-shaped, rodlike with two heads and rodlike with one head (Chen et al, 2016;Dózsa-Farkas et al, 2015;Shen et al, 2011Shen et al, , 2012aShen et al, , 2012bZhang et al, 2018). While the presence/absence of sperm bundles may be a taxonomically useful character to distinguish species in Mesenchytraeus, the differences in shape of these 'regular sperm bundles' are not.…”
Section: Morphogenetic Processes Of Spermathecae and Sperm Bundlesmentioning
confidence: 99%
See 1 more Smart Citation